A comparative analysis of nutritional compositions of colostrums in Jersey and Holstein cows at their first birth in summer - gökçe, gökhan; Anitas, Özgül; Göncu, Serap; Özğul, Yeşim (Progress in Nutrition, 2021)
Colostrum is the first compound released by mammals after birth, nutrient composition and physicochemical properties are variable depending on many factors. Colostrum quality differs among breeds and has become more important in calf performances. The negative effects of hot environments in calves will reduce feed intake, low average daily gain, disease incidence, and morbidity. This negative effect also continues to breeding time, size and age at first calving. A limited number of studies documented the effects of hot condition on modification of colostrum, in particular referred to fatty acids contents.  For this purpose, this study was designed to compare fatty acids contents of Holstein and Jersey cattle colostrum during summer months. Our results showed that saturated fatty acids (SFA), monounsaturated fatty acids (MUFA) and polyunsaturated fatty acids (PUFA) were similar in both breeds immediately after birth. However, SFA content was found to be high in Holstein 8 hours and 16 hours after birth in Jersey whereas MUFA and PUFA contents decreased in colostrum taken at 8 days after birth in the Holstein breed and 16 hours after birth in Jersey breed. It can be concluded that colostrum immediately taken after birth are rich in fatty acids, especially, MUFA and PUFA.